Purificação, caracterização e aplicação da endoglucanase de Botrytis ricini URM 5627 - Silva, Tatielle Pereira (2020)
Cellulases are hydrolytic enzymes of the cellulolytic complex that cleave cellulose O-glycosidic bonds, being divided into three groups, according to their site of action on the cellulosic substrate: endoglucanases (EnG), which initiate hydrolysis and cleave internal bonds cellulosic fiber, in the amorphous region; exoglucanases (ExG), which act on the outer region of the cellulose; and β-glycosidases (BG), which hydrolyze glucose-soluble oligosaccharides. Brazilian agriculture has consolidated itself as the major vector of development in the country. This large production consequently generates a quantity of residues that in turn are responsible for a portion of the pollution and degradation of the environment. In this study, in the first article we sought to isolate a new endoglucanase from the filamentous fungus Botrytis ricini URM 5627 using liquid protein chromatography, then biochemical characterization was carried out, regarding optimal temperature, thermostability, optimum pH, pH stability , salt effect, halotolerance, kinetic constants, and the pure enzyme was applied in the saccharification of agro-industrial residues. In the second article, the effects of acid and biological pretreatment were observed in obtaining fermentable sugars. In the third article, the effects of Box-Behnken statistical planning on the optimization of enzymatic saccharification of wheat bran were observed. A halotolerant endoglucanase with a molecular mass of 39 kDa was isolated. It was obtained from the solid fermentation of the sugarcane bagasse by the fungus Botrytis ricini URM 5627. After the isolation, the biochemical characterizations were performed, presenting optimum temperature and pH of 50oC and 5, respectively. The enzyme was stable in a range of 39 to 60oC for 60 min and between pHs 4 to 6. The enzyme activity increased in the presence of Na +, Mn2 +, Mg2 +, Zn2 + and decreased when in the presence of Ca2 +, Cu2 + and Fe2 + ions . Endoglucanase showed a halotolerant profile, since its activity was increased as the NaCl concentration increased. The enzyme was able to saccharify all the tested residues. The biological pretreatment using Botrytis ricini URM 5627 showed a great superiority to the acid pretreatment in the cellulose exposure as seen in the results obtained. Box-Behnken planning successfully determined the conditions of the variables: saccharification time, substrate loading and enzymatic loading, necessary to maximize the production of reducing sugars. This work made it possible to obtain a highly active enzyme capable of being applied to obtain fermentable sugars.